Autoinhibition of the formin Cappuccino in the absence of canonical autoinhibitory domains. - Bor, B.; Vizcarra, C.L.; Phillips, M.L.; Quinlan, M.E. (Molecular Biology of the Cell, 2012)
Formins are a conserved family of proteins known to enhance actin polymerization. Most formins are regulated by an intramolecular interaction. The Drosophila formin, Cappuccino (Capu), was believed to be an exception. Capu does not contain conserved autoinhibitory domains and can be regulated by a second protein, Spire. We report here that Capu is, in fact, autoinhibited. The N-terminal half of Capu (Capu-NT) potently inhibits nucleation and binding to the barbed end of elongating filaments by the C-terminal half of Capu (Capu-CT). Hydrodynamic analysis indicates that Capu-NT is a dimer, similar to the N-termini of other formins. These data, combined with those from circular dichroism, suggest, however, that it is structurally distinct from previously described formin inhibitory domains. Finally, we find that Capu-NT binds to a site within Capu-CT that overlaps with the Spire-binding site, the Capu-tail. We propose models for the interaction between Spire and Capu in light of the fact that Capu can be regulated by autoinhibition.